A Novel Method for the Description of Voltage-Gated Ionic Currents Based on Action Potential Clamp Results—Application to Hippocampal Mossy Fiber Boutons - Clay, John R. (Frontiers in Cellular Neuroscience, 2016)
Action potential clamp (AP-clamp) recordings of the delayed rectifier K+ current IK and the fast-activated Na+ current INa in rat hippocampal mossy fiber boutons (MFBs) are analyzed using a computational technique recently reported. The method is implemented using a digitized AP from an MFB and computationally applying that that data set to published models of IK and INa. These numerical results are compared with experimental AP-clamp recordings. The INa result is consistent with experiment; the IK result is not. The difficulty with the IK model concerns the fully activated current-voltage relation, which is described here by the Goldman-Hodgkin-Katz dependence of the driving force (V-EK) rather than (V-EK) itself, the standard model for this aspect of ion permeation. That revision leads to the second - a much steeper voltage dependent activation curve for IK than the one obtained from normalization of a family of IK records by (V-EK). The revised model provides an improved description of the AP-clamp measurement of IK in MFBs compared with the standard approach The method described here is general. It can be used to test models of ionic currents in any excitable cell. In this way it provides a novel approach to the relationship between ionic currents and membrane excitability in neurons.